2019
DOI: 10.3390/atmos10050260
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical Structures of Gravity Waves Produced by Typhoon Soudelor in 2015 near Taiwan

Abstract: Tropical cyclones (TCs) are complex sources of atmospheric gravity waves (GWs). In this study, the Weather Research and Forecasting Model was used to model TC Soudelor (2015) and the induced elliptical structures of GWs in the upper troposphere (UT) and lower stratosphere (LS) prior to its landfall over Taiwan. Conventional, spectral and wavelet analyses exhibit dominant GWs with horizontal and vertical wavelengths, and periods of 16–700 km, 1.5–5 km, and 1–20 h, respectively. The wave number one (WN1) wind as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…lat). Now, in effort to examine the presence of upward propagating GWs from this deep convective region, the vertical temperature profiles obtained from GPS-RO measurements at an altitude range of 10-40 km were filtered using a high pass fourth-order Butter-worth filter with a cut-off at 7 km (Ming et al, 2019). Figures 6a and 6d show the geographic locations of three available GPS-RO soundings close to TC Victoria superimposed on the half hourly averaged brightness temperature at 11 UT on 8 and 9 April, respectively.…”
Section: 1029/2020ja028003mentioning
confidence: 99%
“…lat). Now, in effort to examine the presence of upward propagating GWs from this deep convective region, the vertical temperature profiles obtained from GPS-RO measurements at an altitude range of 10-40 km were filtered using a high pass fourth-order Butter-worth filter with a cut-off at 7 km (Ming et al, 2019). Figures 6a and 6d show the geographic locations of three available GPS-RO soundings close to TC Victoria superimposed on the half hourly averaged brightness temperature at 11 UT on 8 and 9 April, respectively.…”
Section: 1029/2020ja028003mentioning
confidence: 99%
“…Intrusion of water vapor into the stratosphere has significant impact on the climate change. The hodograph method can suggest the vertical energy propagation direction of GWs, as per linear dispersion relation of GW (Chane Ming et al, ; Ganguly et al, ; Vincent & Joan Alexander, ). An earlier study over Kolkata using radiosonde observations revealed that convective activities enhanced relative humidity in LS (Ganguly et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also seen that gravity wave energy produced during tropical cyclones is higher than generated by local convections (Chane‐Ming et al, ). Researchers have also reported the sensitivity of the atmospheric chemistry and climate on the changing tropical lower stratosphere (Chane Ming et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After the early period of interest in gravity waves as a mechanism for spiral bands, the large majority of research on TCs and gravity waves was concerned with the deeper, longer waves that propagate upward into the stratosphere and mesosphere (e.g., Pfister et al 1993; Kim and Chun 2005;Kim et al 2009;Kuester et al 2008;Chane Ming et al 2010;Niranjan Kumar et al 2011;Chane Ming et al 2019). These generally have wavelengths from tens to hundreds of kilometers.…”
Section: Introductionmentioning
confidence: 99%